PNO1 inhibits autophagy-mediated ferroptosis by GSH metabolic reprogramming in hepatocellular carcinoma - Hu, Xiaomeng; He, Yuchao; Han, Zhiqiang; Liu, Wei; Liu, Dongming; Zhang, Xihao; Chen, Lu; Qi, Lisha; Chen, Liwei; Luo, Yi; Li, Qiang; Chen, Peng; et al. (Cell death & disease, 2022)
Effective strategies for hepatocellular carcinoma, which is the second leading cause of death worldwide, remain limited. A growing body of emerging evidence suggests that ferroptosis activation is a novel promising approach for the treatment of this malignancy. Nevertheless, the potential therapeutic targets and molecular mechanisms of ferroptosis remain elusive. In this study, we found that PNO1 is a bona fide inhibitor of ferroptosis and that autophagy induced by PNO1 promotes cystine/glutamate antiporter SLC7A11 while increasing the synthesis and accumulation of intracellular glutamate. This increase is followed by an equally proportional addition in cystine uptake, which consequently enhances system Xc - activity that leads to the inhibition of ferroptosis. In the maintenance of redox homeostasis, system Xc - activated via PNO1-autophagy metabolism is responsible for maintaining cysteine for glutathione (GSH) synthesis, and the final GSH metabolic reprogramming protects HCC cells from ferroptosis. The combination of PNO1 inhibition with drugs causing ferroptosis induction, particularly sorafenib, the first-line drug associated with ferroptosis in liver cancer shows therapeutic promise in vitro and in vivo. Together, our findings indicated that PNO1 protects HCC cells from ferroptotic death through autophagy-mediated GSH metabolic remodeling, and we identified a candidate therapeutic target that may potentiate the effect of ferroptosis-based antitumor therapy.